Acceptance & use of I-learn for academic purposes among students in Universiti Teknologi MARA (UiTM) Cawangan Melaka / Muhammad Faizan Mahadi - Mahadi, Muhammad Faizan (Faculty of Business and Management, 2018)
The usage of i-Learn is common for Universiti Teknologi Mara (UiTM) students as a platform of e-learning. However, there are still students who are unaware of the usage of i-Learn for academic purposes and its other useful features. This study thus aims to investigate the relationship between four acceptance factors towards the acceptance & use of I-Learn for academic purposes among students in UiTM Cawangan Melaka. In this study, the researcher used four acceptance factors, which are performance expectancy, effort expectancy, social influence and facilitating condition, as proposed in the Unified Theory of Acceptance and Use of Technology. The study put to use questionnaire as the research instrument and were distributed to 370 students from three different campuses in UiTM Cawangan Melaka which is Kampus Bandaraya, Kampus Alor Gajah, and Kampus Jasin. The findings is then analysed and showed that all of the variables proposed are related to the dependent variable. This study also resolved that facilitating condition is the most significant factor that contribute to the acceptance and use of i-Learn for academic purposes among students in UiTM Cawangan Melaka.